Exploring Factors Influencing ERP System Adoption and Its Influence on Operational Efficiency: A Case Study of a Medical Equipment Supplier - Rhendy Akhmad Firdaus; Indupurnahayu Indupurnahayu; Renea Shinta Aminda (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
The implementation of an Enterprise Resource Planning (ERP) system serves as a crucial strategy for companies looking to enhance their efficiency, effectiveness, and competitive edge. This study aims to identify the factors that influence ERP system implementation and their subsequent impact on work effectiveness. To achieve this, the research employs a quantitative descriptive method, which involves distributing questionnaires to collect data from respondents. The collected data undergo various analyses, including validity tests, normality tests, and multiple linear regression tests. The findings reveal that organizational characteristics, information quality, and management support significantly and positively influence work implementation. Conversely, the HR competency variable did not demonstrate a significant or positive effect. Additionally, the study reveals that ERP implementation positively affects work effectiveness. This indicates that adopting an ERP system allows companies to streamline their data processing, ultimately leading to improved work performance. By integrating these systems, organizations can enhance their operational efficiency, thereby fostering a more productive work environment. Overall, the study highlights the importance of leveraging ERP systems to bolster work effectiveness and underscores the critical role that organizational factors play in this process.